Determinasi Nilai Perusahaan: Peran Akuntansi Lingkungan, Leverage, dan Kebijakan Dividen pada Perusahaan Pertambangan di Indonesia - Sitti Mispa; Sri Sundari; Kartini Kartini (Al-Buhuts, 2025)
This study aims to analyze the effect of environmental accounting, leverage, and dividend policy on firm value, both partially and simultaneously, in mining sector companies listed on the Indonesia Stock Exchange. A quantitative approach was employed using multiple linear regression analysis on secondary data from 2017 to 2022. The results show that, partially, environmental accounting and dividend policy have a positive and significant effect on firm value. Leverage displays varied effects depending on the individual company’s capital structure. Simultaneously, the three independent variables explain 57.8% of the variability in firm value (R² = 0.578), indicating a strong predictive model. These findings support stakeholder theory and signaling theory, offering significant implications for corporate management, investors, and regulators in formulating sustainable and financial strategies for mining companies.